ECOLOGICAL TOURISM AS A PRIORITY AREA OF SUSTAINABLE TOURISM DEVELOPMENT IN UKRAINE: CURRENT CHALLENGES - PANKIV, Natalia; SKRYPNYK, M. (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the problems of ecological tourism development in Ukraine and ways to solve them. The positive and negative consequences of the development of ecological tourism are studied and the prospects for the development of ecological tourism in Ukraine are outlined. In particular, it was emphasized that the aggravation of environmental problems of tourism requires the search for new vectors of development. One of them is the application in tourism of the basic principles of the concept of sustainable development, which meets the needs of today and does not endanger the needs of future generations. The sustainable development strategy focuses on realizing the two most important goals. First of all, efficient and rational use of resources and their potential, as well as the optimal solution to regional development issues. These two goals can be achieved through the development of ecological tourism, as it will be possible to preserve the unique beauty of natural areas, reduce anthropogenic pressure on the environment, improve the welfare of local people, and more.Ukraine has sufficient ecotourism resources, the use of which, along with the growing demand for tourism services, will naturally lead to the intensification of infrastructure development and territorial organization of ecotourism activities. The concept of ecotourism emphasizes the need to preserve natural and cultural heritage, and biodiversity and improve the ecological, social, and economic status of the regions visited by ecotourists. Ecological tourism should become a model for reorganization, and greening of the entire tourism industry. Sustainable ecologically balanced tourism should become not only a philosophy but also a leading management strategy for tourism development.In recent years, the sphere of tourism in Ukraine has been going through difficult times. The Covid-19 pandemic has become a challenge for the tourism industry, making domestic travel, including ecotourism, more prevalent in Ukraine. The next terrible event for Ukraine was the war. Several hundred crimes against the environment prohibited by the Geneva Convention as a result of Russian aggression have been recorded since the beginning of the full-scale invasion of Russian troops into the country. After our victory, in the conditions of growing needs of the population in recreation and tourism, extensive and intensive interaction of society and nature, there is a well-founded need for systematic use of natural resources through the use of appropriate mechanisms of sustainable nature, one of which is ecologically oriented tourism. aimed at implementing the conceptual foundations of sustainable development.
Keywords: ecological tourism (ecotourism); sustainable development strategy; Ukraine; preservation of the environment; sustainable development of tourism; ecotourism activities; environment; nature reserves; tourist natural resources; ecologically oriented; socio-economic criteria; tourist potential